Cost-Utility Analysis of Once-Weekly Semaglutide, Dulaglutide, and Exenatide for Type 2 Diabetes Patients Receiving Metformin-Based Background Therapy in China - Hu, Shanshan; Wang, Shuowen; Qi, Chendong; Gu, Shengying; Shi, Chenyang; Mao, Lin; Fan, Guorong (Frontiers in Pharmacology, 2022)
Introduction The substantial financial burden associated with type 2 diabetes (T2D) over a lifetime cannot be neglected. Therefore, the objective of this study was to evaluate the pharmacoeconomic value of three once-weekly GLP-1 RAs, namely, subcutaneous semaglutide (sc. SEMA), dulaglutide (DULA) and extended-release exenatide (e-r EXEN), in treating patients with T2D that cannot be controlled with metformin-based background therapy and to find the suitable price reduction for non-cost-effective medications, to provide the administration reasonable recommendations to adjust drug prices. Methods The baseline characteristics of the simulation patient cohort were sourced from a comprehensive meta-analysis synthesizing 453 trials evaluating 21 hypoglycemic agents from 9 categories of drug. The UKPDS OM2 was applied to project the long-term effectiveness and costs from a Chinese health care provider’s perspective. After cost-utility analysis, the reasonable price adjustment of non-cost-effective options was explored via binary search. Uncertainty was measured by means of sensitivity analysis. Results After a 40 years simulation, group sc. SEMA, DULA and e-r EXEN yielded 9.6315, 9.5968 and 9.5895 years of QALYs, respectively. In terms of expenditure, the total costs for group sc. SEMA, DULA and e-r EXEN were $42012.47, $24931.27 and $40264.80, respectively. DULA was dominant over e-r EXEN due to the higher QALYs and lower total costs. The ICURs of sc. SEMA vs. DULA and sc. SEMA vs. e-r EXEN were $492994.72 and $41622.69 (ICUR > λ), respectively, indicating that sc. SEMA was not more cost-effective than DULA or e-r EXEN. The INMB and absolute NMB yield the same conclusions which were robust to one-way and probabilistic sensitivity analyses. After several assumptions in the binary search, sc. SEMA and e-r EXEN appear to become cost-effective when their annual costs are decreased by 57.63% and 70.34%, respectively, with DULA as a counterpart. Conclusion From the cost-utility analysis, DULA appears to be the most cost-effective option among sc. SEMA, DULA and e-r EXEN for the treatment of patients with T2D receiving metformin-based background therapy. If there were 57.63% or 70.34% reductions in the cost of sc. SEMA or e-r EXEN, respectively, they would become as cost-effective as DULA in China.